Proton NMR studies of intact cells - Brindle, K; Brindle, Kevin M. (1982)
﻿ The technique of 1H spin echo n.m.r. has been used for the non-invasive study of enzyme catalysed 1H/2H equilibrium isotope exchange at the C-2 position of lactate in suspensions of human erythroeytes. The intracellular environment of the enzymes involved in this exchange has been investigated by comparing the exchange properties of the enzymes in the intact cell with the properties they display in vitro. A study of the exchange of the lactate C-2 substituent with solvent, which is catalysed by a coupled system of four glycolytic enzymes, has teen used to examine the kinetic properties of the individual enzymes in vitro. Measurements of the exchange in the intact cell have been used to investigate the in situ kinetic properties of one of these enzymes, glyceraldehydephosphate dehydrogenase. Contrary to the conclusions of previous studies with the isolated enzyme in vitro, these measurements have shown that the enzyme is not rate determining for glycolytic flux in the human erythrocyte and that it is unlikely that it is bound to the cell membrane in situ. A study of 1H/2H exchange between the C-2 positions of methyl labelled lactate molecules, catalysed by lactate dehydrogenase, has been used to investigate the in situ kinetic properties of this enzyme. Comparison of these properties with those it displays in vitro indicate that the free intracellular NAD(H) concentration in the erythrocyte is only approximately 10% of the total extractable concentration. A considerable fraction of the coenzyme must be bound, therefore, in the intact cell. This type of experiment should be widely applicable to a variety of tissues and possibly to different dehydrogenases. Theoretical aspects of bulk isotope exchange kinetics in multi-enzyme systems are examined and the effects of chemical flux, and of isotope effects, on the measurement of isotopic flux are considered. The advantages of the n.m.r. method over conventional radioactive tracer techniques are described. It is concluded that 1H n.m.r. studies of 1H/2H isotope exchange may be used to obtain information about the kinetic properties of enzymes in intact cellular systems. The technique should be a useful complement, therefore, to the currently more widely used n.m.r. methods employing the 31P and 13C nuclei and to other methods used for the non-invasive study of metabolism.